Analysis Of The Financial Performance Of Jaya Mandiri Village Owned Enterprises (Bumdes) In Jambu Village, Merigi Kelindang Sub-District, Bengkulu Tengah District - Aini, Faizah; Reswita, Reswita; Windirah, Nola (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
This study aims to: compile the financial reports of Jaya Mandiri BUMDes in Jambu Village, Merigi Kelindang District, Central Bengkulu Regency in accordance with Indonesian Financial Standards, to: analyze the financial performance of Jaya Mandiri BUMDes in Jambu Village, Merigi Kelindang District, Central Bengkulu Regency. The data collected are primary data and secondary data. The data analysis used is the balance sheet to find out exactly how much assets, debts and capital it has at a certain time. Profit and loss report to find out profit and loss in the financial statements. The liquidity ratio (Liquidity Ratio) for the company's ability to meet short-term (debt) obligations. Current Ratio (Current Ratio) to measure the company's ability to pay short-term obligations or debts that are due soon when billed as a whole. Solvency Ratio (Leverage Ratio) to measure the extent to which the company's assets are financed with debt. The ratio of debt to assets (Debt to Assets Ratio) to determine the company's ability to pay off all of its debts guaranteed by the amount of the company's assets. Debt to Equity Ratio (Debt to Equity Ratio) to show what part of the capital is collateral for cooperative debt or illustrates the extent to which the owner's capital can cover debts to outsiders. Rentability Ratio (Rentability Ratio) to see the company's ability to earn profits in relation to sales, total assets, and own capital. Net Profit Margin (Net Profit Margin) to show the company's net income from sales. Return On Equity (ROE) to compare the Remaining Results of Operations with the amount of Capital. The results of the analysis of financial statements on net profit obtained the highest net profit in 2019 with a value of Rp. 18,207,525 whereas in 2018 with the lowest net profit value it only reached Rp. 4,845,625, the balance sheet obtained the highest total assets and liabilities in 2019 of Rp. 151,207,525 and the lowest in 2017 was Rp. 51,654,375. Based on the results of the analysis of financial performance on the calculation of the net profit margin in the last 5 years, the net profit margin has fluctuated with very good criteria. quite good because the use of business capital is appropriate enough to generate profits.